2004
DOI: 10.1088/1475-7516/2004/01/003
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of second-order cosmological perturbations and non-Gaussianity

Abstract: We present a second-order gauge-invariant formalism to study the evolution of curvature perturbations in a Friedmann-Robertson-Walker universe filled by multiple interacting fluids. We apply such a general formalism to describe the evolution of the second-order curvature perturbations in the standard one-single field inflation, in the curvaton and in the inhomogeneous reheating scenarios for the generation of the cosmological perturbations. Moreover, we provide the exact expression for the second-order tempera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
128
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(132 citation statements)
references
References 51 publications
(271 reference statements)
4
128
0
Order By: Relevance
“…Although we concentrate on the mixed model of the inflaton and the curvaton in this paper, other mixed model may also be worth investigating. In particular, large non-Gaussianity can also be generated in the modulated reheating [62,63,64,27] and preheating scenarios [65,66,67] so that the implications of such a mixed model on the inflationary parameters and non-Gaussianity are of great interest and will be presented elsewhere [68].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Although we concentrate on the mixed model of the inflaton and the curvaton in this paper, other mixed model may also be worth investigating. In particular, large non-Gaussianity can also be generated in the modulated reheating [62,63,64,27] and preheating scenarios [65,66,67] so that the implications of such a mixed model on the inflationary parameters and non-Gaussianity are of great interest and will be presented elsewhere [68].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…These have been studied in great detail [14][15][16][17][18][19] and, even though approximate solutions have been found in specific limits [20][21][22][23][24][25][26][27][28][29], they require a numerical treatment. Numerical convergence is now being reached as the latest codes [30][31][32][33] obtain consistent results.…”
Section: Introductionmentioning
confidence: 99%
“…To accomplish this, the second order cosmological perturbation theory is necessary. So, the perturbation theory beyond the linear order has been investigated by many authors [3,4,5,6] and is a topical subject, in particular, to study the non-Gaussianity generated during the inflation [7] and that will be observed in CMB data [8].In this letter, we show the gauge invariant formulation of the general relativistic second order cosmological perturbations on Friedmann-Robertson-Walker (FRW) universe filled with the perfect fluid. This short letter is prepared to show the aspect of the special importance of our companion paper [10], briefly.…”
mentioning
confidence: 98%
“…To accomplish this, the second order cosmological perturbation theory is necessary. So, the perturbation theory beyond the linear order has been investigated by many authors [3,4,5,6] and is a topical subject, in particular, to study the non-Gaussianity generated during the inflation [7] and that will be observed in CMB data [8].…”
mentioning
confidence: 99%